Ruffier test model taking into account an age of the patient - Заневський, І. П.; Заневська, Л. Г. (Physical Education Theory and Methodology, 2013)
There are presented the results of the comparative analysis of the existing methods of correcting the values of Ruffier index for the children teenagers. The model of the correction of the value of Ruffier index and the model of the correction of the gradation of the estimations of Ruffier test taking into account an age of the patient are proposed. It is shown that the parameter of the correction of the value of Ruffier index and gradations of the estimations of the corresponding test must be a relationship of the standard pulse rate in the state of calmness, accepted for the age class of patient, to the standard pulse rate of adult person. The corresponding model of the estimation of the functional state of the cardiovascular system of persons of school age showed a statistically significal (p < 0,001) correction of the value of Ruffier index and the gradation of the levels of health relatively to the conventional model for the adult, which is recommended. The quantitative assessment of the consequences of correction in the distribution of students on levels and groups of health is represented.